Effects of Perceptual Fluency on Affective Judgments - Reber, Rolf; Winkielman, Piotr; Schwarz, Norbert (Psychological Science, 1998)
According to a two-step account of the mere-exposure effect, repeated exposure leads to the subjective feeling of perceptual fluency, which in turn influences liking. If so, perceptual fluency manipulated by means other than repetition should influence liking. In three experiments, effects of perceptual fluency on affective judgments were examined. In Experiment 1, higher perceptual fluency was achieved by presenting a matching rather than nonmatching prime before showing a target picture. Participants judged targets as prettier if preceded by a matching rather than nonmatching prime. In Experiment 2, perceptual fluency was manipulated by figure-ground contrast. Stimuli were judged as more pretty, and less ugly, the higher the contrast. In Experiment 3, perceptual fluency was manipulated by presentation duration. Stimuli shown for a longer duration were liked more, and disliked less. We conclude (a) that perceptual fluency increases liking and (b) that the experience of fluency is affectively positive, and hence attributed to positive but not to negative features, as reflected in a differential impact on positive and negative judgments.